Soil Nutrient Indices and Fertilizer Requirements of Different Common Crops of South-East Rajasthan - Sharma, C. P.; Singh, Harvinder; Pareek, B. L.; Seth, S. P. (Indian Forester, 1977)
On the basis of soil tests carried out in the four districts of South-East. Rajasthan, the total requirement of fertilizers have been calculated as 57624.06, 36754.69 and 23238.80, tonnes of Nitrogen (N), Phosphorus (P2O5) and Potash (K2O) respectively. These calculations are based on the crop pattern suggested for the area on the one hand and fertility levels of the soils on the other and this reveals that there is sample scope for the use of fertilizers in these areas so that average yield can be increased. The fertilizer recommendations for the common crops of the region have also been suggested.